Comparative sectoral price elasticities of U.S. energy demand - Kwame Asiam Addey; Saleem Shaik; Kekoura Sakouvogui (Cogent Economics & Finance, 2019)
A sustainable energy system is key for addressing the world's environmental and social challenges. The U.S is the second largest consumer of energy, with increased energy consumption in the previous half-century. To curb energy demand, it is essential to understand the relative price elasticities among the four main U.S energy consumption sectors; residential, industrial, commercial and transportation. The aim of this study is to present a theory-based comparative analysis of U.S sectoral energy price elasticities using the pooled mean group model. The speed of adjustment for the four sectors were -0.43, -0.41, -0.55 and -0.37, suggesting the existence of long-run relationships. The short-run own-price elasticities were -0.17, -0.39 and -0.27 for the commercial, industrial and residential sectors while the long-run own-price elasticities were -0.33, -0.45 and -0.20 for the commercial, residential and transportation sectors. We conclude that the residential sector readjusts to long-run equilibrium at a faster rate than the three other sectors. In the long run, this sector will yield a higher response to a price change. We suggest that price policies aimed at reducing energy demand should primarily target the residential sector, followed by the commercial and transportation sectors.
Keywords: E64; N7; Q41; 330; elasticity; PMG; energy demand; speed of adjustment; 48 U.S. states; 1970 to 2015